(untitled) (Global Journal of Management and Business Research, 2022)
Social capital and capability development have been determined as effective business orientation enablers in achieving good business performance To understand the effect of entrepreneurial orientation on business performance there were a number of findings that were recorded in this research based on the notable variables Six hundred questionnaires were provided to SMEs in Nigeria where 67 of the population provided their honest and reliable opinion